Analysis of the phenotypic traits of 20 crabapple varieties (Malus spp.) - ZHAO Dandan; ZHANG Yanwen; HU Yifei; WU Xiaojun; LIU Weichao; ZHANG Kaiming; LI Fei (Guoshu xuebao)
[Objective] The aim of the present experiment was to explore the fruit application value of different crabapple varieties and make full use of crabapple resources. [Methods] With 20 crabapple varieties in Zhengzhou as experimental materials, the fruit color of different varieties at the fruit ripening stage was observed, and single fruit mass, fruit transverse diameter, fruit longitudinal diameter, volume, soluble solid substances, titrated acid, vitamin C, peel hardness, flesh hardness and 15 other quality indicators were determined. Comprehensive analysis and evaluation of fruits of different varieties were conducted via cluster analysis and principal component analysis. [Results] Perfect Purple crabapple entered the fruit ripening stage at the end of August, which was the earliest to enter the fruit ripening stage. Profusion entered the final stage of fruit shedding at the latest stage, and its fruit hanging period was the longest, reaching 232 days. Adams, Jewelcole, Indian Magic, Indian Summer, Golden Fairy, Evereste and Royal Beauty fruits could hang on the tree until the following year. The fruit color upon maturity is mostly red to varying degrees. The mass of 20 crabapple varieties was 0.47-7.86 g, the volume ranged from 0.42 to 6.67 mL, the fruit transverse diameter ranged from 9.46 to 24.91 mm, the fruit longitudinal diameter ranged from 8.36 to 22.04 mm, the fruit shape index ranged from 0.78 to 1.05, the length of the fruit stem ranged from 24.74 to 41.79 mm, the thickness of the fruit stem ranged from 0.53 to 2.98 mm, the hardness of the peel ranged from 656.24 to 2 460.05 g, the fragility of the peel ranged from 7.98-22.64 mm, the hardness of the flesh ranged from 331.60-2 390.27 g, the fragility of the flesh ranged from 175.99 to 2143.17 mm, the soluble solids content ranged from 11.90% to 22.43%, the titratable acid content ranged from 0.82% to 2.80%, the solid/acid ratio ranged from 0.32 to 16.00%, the vitamin C contents ranged from 0.00 to 322.33 mg·g-1. The fruit phenotypes of the different crabapple varieties varied significantly, with coefficients of variation ranging from 8.05% to 89.74%. Among them, the single fruit mass had the largest coefficient of variation, whereas the fruit shape index had the smallest coefficient. The cluster analysis revealed that at the European distance of 15, crabapple fruit can be divided into four categories. The correlation analysis revealed that the longitudinal diameter of the fruit was significantly and positively correlated with the fruit transverse diameter; the fruit volume was significantly and positively correlated with the fruit transverse diameter and fruit longitudinal diameter; the single fruit mass was significantly and positively correlated with the fruit transverse meridian, fruit longitudinal diameter and fruit volume; the titratable acid content was negatively correlated with the transverse diameter; the solid/acid ratio was significantly and negatively correlated with the titratable acid content; the fruit peel fragility was significantly and positively correlated with the fruit transverse meridian, fruit longitudinal diameter, fruit volume, and single fruit mass and negatively correlated with the titratable acid content; the flesh hardness was significantly and positively correlated with the peel hardness and significantly and negatively correlated with the fruit transverse diameter, fruit longitudinal diameter, fruit volume, single fruit mass and fragility of the fruit peel; and the flesh fragility was significantly and positively correlated with the flesh hardness. The five principal components were extracted from the 15 quality indices of 20 different varieties, and the cumulative variance contributed 84.298%. The characteristic value of PC1 was 6.226, and the contribution rate was 41.505%. The indicators with large absolute values of the eigenvector were the fruit transverse diameter, fruit longitudinal diameter, fruit volume and single fruit mass. PC1 mainly reflects the size, volume and mass of crabapple fruit. The characteristic value of PC2 was 2.334, and the contribution rate was 15.558%. The indicators with large absolute values of the eigenvectors were the solid/acid ratio, vitamin C content and titratable acid content. PC2 mainly reflects the nutritional value and flavor of crabapple fruit. The characteristic value of PC3 was 1.699, and the contribution rate was 11.328%. The indices with large absolute values of the eigenvector were hardness and flesh fragility. PC3 mainly reflects the taste and texture of the crabapple fruit. The characteristic value of PC4 was 1.357, and the contribution rate was 9.049%. The index with large absolute values of the feature vector was the length of the stem and the thickness of the stem. The characteristic value of PC5 was 1.029, the contribution rate was 6.857%, and the index with a large absolute value of the eigenvector was the fruit shape index. Principal component analysis revealed that the main factors affecting fruit quality were fruit size, the solid acid ratio and vitamin C content. [Conclusion] Among the 20 crabapple varieties, Evereste, Royal Beauty, Indian Summer, Indian Magic, Jewelcole, Adams and Golden Fairy have a long fruit hanging period and can be used as fruit-ornamental varieties. Eleyi, Selkirk, Evereste and other varieties possess the characteristics of large fruits and low peel hardness and can be developed in the direction of fresh fruit consumption. Profusion and Rudolph have a reasonable solid/acid ratio and high vitamin content, which are suitable for development toward edible fruit processing.